(untitled) (ModaPalavra e-periódico, 2022)
This article is the result of applied research with students from the first and third semesters of the Technical Course in Modeling at a Federal institution in Santa Catarina, located in the Itajaí Valley, in order to understand their understanding of the creative economy of Fashion in the region. The contact with the students was made previously by one of the authors, as a teacher of the curricular unit of Manual Modeling and, perceived interest of the students in undertaking business after graduation, they were understood as a possible public of creative economy actions. Information on local perceptions about the creative economy of Fashion are of interest to the Municipal Councils of Cultural Policies, and can assist in the construction of public policies for the region. The research took place via an online questionnaire with 35 students. The method of analysis used was content analysis by Bardin (2016), which allowed us to observe the predominance of the discourse of entrepreneurship, whose impediments were the investment in time and money. The research reveals the understanding of the creative economy of Fashion linked to fairs and handicrafts, to the detriment of industrial development policies applied in the region.